Interprofessional mental health training in rural primary care: findings from a mixed methods study. Issue 3 (May 2015) - Heath, Olga; Church, Elizabeth; Curran, Vernon; Hollett, Ann; Cornish, Peter; Callanan, Terrence; Bethune, Cheri; Younghusband, Lynda
Abstract The benefits of interprofessional care in providing mental health services have been widely recognized, particularly in rural communities where access to health services is limited. There continues to be a need for more continuing interprofessional education in mental health intervention in rural areas. There have been few reports of rural programs in which mental health content has been combined with training in collaborative practice. The current study used a sequential mixed-method and quasi-experimental design to evaluate the impact of an interprofessional, intersectoral education program designed to enhance collaborative mental health capacity in six rural sites. Quantitative results reveal a significant increase in positive attitudes toward interprofessional mental health care teams and self-reported increases in knowledge and understanding about collaborative mental health care delivery. The analysis of qualitative data collected following completion of the program, reinforced the value of teaching mental health content within the context of collaborative practice and revealed practice changes, including more interprofessional and intersectoral collaboration. This study suggests that imbedding explicit training in collaborative care in content focused continuing professional education for more complex and chronic health issues may increase the likelihood that professionals will work together to effectively meet client needs.